2019
DOI: 10.2174/1566524019666190308110122
|View full text |Cite
|
Sign up to set email alerts
|

Novel GLI3 Mutations in Chinese Patients with Non-syndromic Post-axial Polydactyly

Abstract: Background: Polydactyly, characterized by supernumerary digits in the upper or lower extremities, is the most common congenital digital abnormalities. It derives from the defective patterning of anteroposterior axis of the developing limb, with various etiology and clinical heterogeneity. The patients with post-axial polydactyly type A (PAPA) have the typical symptom of a well-formed supernumerary digit outside the fifth digit. Objective: The aim of present study was to identify the causative mutations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that GLI3 possesses a dual function, including a transcriptional activator of SHH signaling pathway by phosphorylated full‐length GLI3 and a repressor by C‐terminally truncated CLI3. Recently, several novel mutations of GLI3 have been identified in the patients with PD, including mutation c. 1622C > T (Zou et al, 2019), c.2148delA (Zhao, Xu, Liu, & Li, 2019), c.3437_3453delTCGAGCAGCCCTGCCCC, and c.3997C > T (Chen et al, 2019), c.1180C > TT (Ni et al, 2019). Therefore, our results suggested that this frameshift mutation of GLI3 might be a main reason for preaxial PD type IV phenotype in this Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GLI3 possesses a dual function, including a transcriptional activator of SHH signaling pathway by phosphorylated full‐length GLI3 and a repressor by C‐terminally truncated CLI3. Recently, several novel mutations of GLI3 have been identified in the patients with PD, including mutation c. 1622C > T (Zou et al, 2019), c.2148delA (Zhao, Xu, Liu, & Li, 2019), c.3437_3453delTCGAGCAGCCCTGCCCC, and c.3997C > T (Chen et al, 2019), c.1180C > TT (Ni et al, 2019). Therefore, our results suggested that this frameshift mutation of GLI3 might be a main reason for preaxial PD type IV phenotype in this Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…Several causative genes have been reported to be associated with IPD, including the GLI family zinc nger 3 gene (GLI3, OMIM 165240), zinc nger protein 141 gene (ZNF141, OMIM 194648), IQ domain-containing protein E gene (IQCE, OMIM 617631), GLI family zinc nger 1 gene (GLI1, OMIM 165220), Family with sequence similarity 92, member A (FAM92A, OMIM 617273) and Centrosomal protein 68 (CEP68, OMIM 616889). (3)(4)(5)(6)(7)(8). Among these genes, GLI3 plays a vital role in limb development.…”
Section: Introductionmentioning
confidence: 99%